The Role of Internal Audit in Risk Management Implementation in Regional Government Agencies (OPD) of Indragiri Hilir Regency Ria Febrina - Febrina, Ria (PT. Anagata Sembagi Education, 2026)
This study aims to analyze the role of internal audit as a watchdog, consultant, and catalyst in the implementation of risk management in Regional Government Agencies (OPD) of Indragiri Hilir Regency. Risk management is a fundamental activity for any organization that wishes to achieve its strategic goals and objectives. In the context of local government, internal audit plays a strategic role not only as a supervisory body but also as a consulting partner and catalyst for change. The research employs a quantitative approach using Partial Least Square-Structural Equation Modeling (PLS-SEM) with data collected through questionnaires and interviews distributed to government internal auditors across OPD units in Indragiri Hilir Regency. The population consists of all government internal auditors in the regency, with cluster sampling used as the sampling method. The study examines three independent variables watchdog role (X1), consultant role (X2), and catalyst role (X3) and their influence on risk management implementation (Y) as the dependent variable. Findings are expected to contribute to the body of knowledge on public sector risk management and provide practical guidance for policymakers and practitioners involved in local government governance and accountability.